Gender Equality Education for The Preventive Domestic Violence Against Women and Children - Anggraeni, Dewi; Muna, Nailil (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Violence against women and children in the family continues to persist. This research aims to educate the community through the involvement of activists from the Fatayat and IPPNU organizations, focusing on gender equality education within the family setting as a preventive measure against domestic violence. A qualitative method was employed in this research, utilizing a service-learning approach that actively engaged community participation. The collected data were analyzed using resolution methods. The findings of the research indicate that: firstly, there still exists a gender bias understanding, highlighting the need for gender equality education; secondly, the concept of gender equality should be applied within the family environment through parenting and the education of children; thirdly, gender equality education for the community aligns with the goals of sustainable development in eliminating all forms of violence against both women and children.